A brief Acceptance and Commitment intervention for work-related stress amongst frontline homelessness staff: a single case experimental design series - Reeve, Andy (2020)
Burnout – a syndrome resulting from chronic exposure to work-related stress – is a particular problem in health and social care contexts where it is understood to adversely impact the quality of care delivered and the health of the workforce. Although there has so far been scant research attention on the levels of, and effects due to burnout amongst frontline homelessness workers, the nature of the demands are equivalent and so this is an important population on which to focus. Additionally, burnout research has previously focussed on the deleterious aspects such as exhaustion rather than positive counter-part constructs such as work-engagement.